Evolution of Ransomware Attacks: A Basic Review - Gauri Dhongade; Omprakash Chandrakar; Rajeshree Khande (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Cybersecurity is emerging field now a days. Information Security is important issue in today’s world as everything is in online mode. Online information exchange leads to different types of cyber-attacks like malwares, ransomware, trojan horse etc. Ransomware is one of type of malwares. Ransomware is emerged in recent years as one of the significant cyber threats. It locks the file and data on victims’ machine and make it inaccessible. It denies individual user, corporate offices, government offices, Banks etc entities access to their files and computers. To safeguard data in various organizations, cyber security play’s vital role. Different cyber security techniques and Best Practices can help in maintaining safe cyber environment. Artificial Intelligence and Blockchain Technology together will be useful for safeguarding systems in future. This paper delves into Fundamental concept of ransomware attacks, detection techniques, challenges and future scope.
Keywords: Malware; Ransomware; Artificial Intelligence; Block chain; Cyber security